2014
DOI: 10.1111/ajps.12112
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the Comparative Perspective on Class and Representation: Evidence from Latin America

Abstract: Does it matter that working‐class citizens are numerically underrepresented in political offices throughout the world? For decades, the conventional wisdom in comparative politics has been that it does not, that lawmakers from different classes think and behave roughly the same in office. In this article, we argue that this conclusion is misguided. Past research relied on inappropriate measures of officeholders’ class backgrounds, attitudes, and choices. Using data on 18 Latin American legislatures, we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
160
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(173 citation statements)
references
References 76 publications
7
160
2
4
Order By: Relevance
“…16 Following best practice from previous research, we included various measures of race to account for the complexities of racial classification in Brazil. 17 These measures include (1) the five census (IBGE) categories used in Figure 1; (2) a 0-1 variable for African descent; and (3) a 0-1 variable for Black (Preto) or White (Branco).…”
Section: Measuring Politicians' Racementioning
confidence: 99%
“…16 Following best practice from previous research, we included various measures of race to account for the complexities of racial classification in Brazil. 17 These measures include (1) the five census (IBGE) categories used in Figure 1; (2) a 0-1 variable for African descent; and (3) a 0-1 variable for Black (Preto) or White (Branco).…”
Section: Measuring Politicians' Racementioning
confidence: 99%
“…But what about socio‐economic variables? Recent research on the class background of representatives in the United States and Latin America (Carnes ; Carnes and Lupu ) has shown that legislative behavior of working class representatives differs markedly from that of representatives from white collar professions. Class anchors attitudes towards social spending both for representatives and the represented in the sense that people from working class backgrounds are more in favor of redistributive measures.…”
Section: Descriptive Representation and Educationmentioning
confidence: 99%
“…Democratization is seen as a salve; if it successfully ushers in institutional changes that equalize the right to allocate political and economic resources (Carnes and Lupu 2015;Cheibub, Gandhi, and Vreeland 2010;Freeman and Quinn 2012;Haggard and Kaufman 2012;Hollyer, Rosendorff, and Vreeland 2011;Limongi and Przeworski 1993;O'Donnell, Schmitter, and Whitehead 1986), then it should be the case that political influence and rent-seeking in economically important sectors should dissipate. As the banking sectors of authoritarian regimes are typically controlled by politicians or their cronies (Chekir and Diwan 2014;Haggard and MacIntyre 2001;Morck, Yavuz, and Yeung 2011), the transition to democratization should thus correspond with a loosening of the grip on financial resources by the elite (Dryzek 2009).…”
Section: Introductionmentioning
confidence: 99%